2012
DOI: 10.1208/s12249-012-9761-z
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Binder Properties of Starch Obtained from Cyperus esculentus

Abstract: The purpose of this study was to isolate starch from the tubers of Cyperus esculentus L. and evaluate its physicochemical and binder properties. Extraction of starch using sodium metabisulfite yielded 37 g of starch per 100 g of the tubers. Scanning electron microscopy indicated that Cyperus starch consists of oval to elliptical particles with a smooth surface. Cyperus starch demonstrates a narrow particle size distribution with a mean of 8.25 μm. Cyperus starch conforms well to United States Pharmacopeia stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
79
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 31 publications
2
79
1
4
Order By: Relevance
“…The poor friability of the ASA tablets prepared with Mst corroborate the low crushing strength of the tablets. Unmodified starch is not a favored direct compressible excipient because of its poor flow, compactibility, moisture and lubricant sensitivity (Manek et al 2012). The relative better compactibility impacted by CaPoL may be the reason for the higher crushing strength and nonfriable nature of the ASA tablets compared to that of Mst.…”
Section: Friabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The poor friability of the ASA tablets prepared with Mst corroborate the low crushing strength of the tablets. Unmodified starch is not a favored direct compressible excipient because of its poor flow, compactibility, moisture and lubricant sensitivity (Manek et al 2012). The relative better compactibility impacted by CaPoL may be the reason for the higher crushing strength and nonfriable nature of the ASA tablets compared to that of Mst.…”
Section: Friabilitymentioning
confidence: 99%
“…It is used in many conventional formulations as binder, diluents and disintegrant (Builders et al, 2013b;Manek et al 2012). Some good attributes that make starch attractive for drug delivery applications include biocompatibility, biodegradability, low cost, availability and relative easy modification potentials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High starch content of this plant provide unique functional properties (Manek et al, 2012), cold storage stabilities, and preserves organoleptic properties of foods . The tiger nut oil also has high monounsaturated fatty acids, similar to olive, avocado and hazelnut oil (Ezeh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The tubers of yellow nutsedge contain large amounts of storage nutrients, including starch (42%), oil (30%), sugar (20%), and protein (9%) (Linssen et al, 1989); therefore, yellow nutsedge could potentially become an ideal model to describe the carbon partition in non-seed tissues (Turesson et al, 2010). Previous studies on yellow nutsedge have mostly focused on the morphology (Wills et al, 1980) and cultivation (AyehKumi et al, 2014) of tubers, their application in food (Defelice, 2002), and biochemical analyses of the tubers (Turesson et al, 2010;Manek et al, 2012). In this study, we have reported the cloning and characterization of full-length cDNA and genomic DNA sequences of CeAGPS gene from yellow nutsedge.…”
mentioning
confidence: 99%